Do Concepts Creep to the Left and the Right? Evidence for Ideologically Salient Concept Breadth Judgments Across the Political Spectrum. Issue 3 (April 2023) - Harper, Craig A.; Purser, Harry; Baguley, Thom
Concept creep explains how established social concepts expand to incorporate new phenomena, with such expansions fundamentally changing conceptual definitions and contributing to a loss of a shared social understanding. However, the existing work has focused on concept creep within a small number of categories that are typically more salient for those on the political left. In this work, we examined whether concept creep is a predominantly leftist phenomenon, or whether the same conceptual expansion is present for typically conservative-salient categories, by exploring judgments of concept breadth for a range of social topics. We found evidence for such symmetry when considering concept breadth for categories such as sexual deviance, terrorism, and personal responsibility—with some nuanced exceptions. We discuss our findings in relation to growing political polarization, intergroup relations, and the study of partisan differences using a variety of politically salient stimuli.